Ecologically embedded languages, cumulative grammars and island ecologies1. Issue 2 (2nd July 2016) - Nash, Joshua
Abstract: Ecolinguistics is used to explicate the concepts ecologically embedded language and cumulative grammar . The example of Norf'k, an unfocused contact language with few speakers spoken on Norfolk Island, South Pacific, is employed to reconcile several issues at hand when dealing with language–environment–culture interaction. Examples from Norf'k illustrating connectedness and cohesion between society and environment are given. Norfolk Island's micro-ecolinguistic case study is used to exemplify the effectiveness of small islands as worthwhile case studies for observing geographical and social bounding. The term linguistic and grammatical hamstering, a process of hoarding language forms and content as a result of this linking, is put forward.